Meaning and Message of 'Jemme' - Mulyawan, I Wayan (Lingual Journal of Language and Culture; Vol 2 No 2 (2016), 2016)
Advertising is intended to persuade audiences, readers, viewers or listeners to take action on products, services and ideas. Advertisements include text, audio, video, photography and graphic designs. We will easily find advertisement through some common mediums namely newspaper, magazine, radio, television, internet, billboards, and many other places. Advertisement analysis is divided into textual and contextual analysis. The textual is the analysis of advertisement structure such as headline, illustration, body copy, signature line, and standing details. Based on the analysis JEMME considered to be a complex advertisement taht consist of 5 (five) element. The contextual analysis is the meaning of the advertisement. According to the analysis, JEMME is a fine jewelery with high standard and very suitable for valentine gift.
Keywords: advertisment structure, meaning and message